ENHANCE VILLAGE FINANCIAL SYSTEM REALIZE ACCOUNTABILITY IN PEMATANG SERAI VILLAGE. - Nasution, ANGGI Pratama; Malikhah, Ikhah; Oktari, Denta (Proceeding International Conference of Science Technology and Social Humanities, 2023)
The findings of this study reveal several strategies for achieving success in implementing SISKEUDES in Pematang Serai Village. These strategies include: Enhancing the quality of the village's vision, mission, and goals to prioritize national/regional development issues in line with the available resources. Improving the quality of the Village Work Program, as outlined in the Regional Long-Term Development Plan (RJPMD) and the Annual Village Government Work Plan (RKP). This involves analyzing the potential for income growth and maximizing village expenditure efficiency. Enhancing the quality of human resources involved in producing SISKEUDES information through continuous support and assistance from the Financial and Development Supervisory Agency (BPKP). Collaborating with educational institutions to foster the development of high-quality human resources through various cooperation programs. In summary, this study identifies strategies to promote the successful implementation of the Village Financial System (SISKEUDES) in Pematang Serai Village. By focusing on improving the village's vision, optimizing the Village Work Program, enhancing human resources, and fostering collaboration with educational institutions, the aim is to enhance accountability and financial management in the village.